Schouten Bracket of Holomorphic Tensors of a Kahlerian Manifold - Jorga Ibrahim (Institute for Research and Community Services (LPPM) ITB, 1974)
Abstract. It is shown that the Schouten bracket of holomorphic tensors of a compact kahlerian manifold W defines a structure of graded complex Lie algebra on the space of holomorphic tensors of the manifold. We obtain an important proposition which generalizes a wellknown result of Lichnerowicz [6,7].Ringkasan. Kita perlihatkan bahwa